Gentrification of station areas and its impact on transit ridership - Chava, J.; Newman, Peter; Tiwari, Reena (Elsevier Ltd, 2018)
© 2018. Transit and transit-oriented developments (TODs) are gaining momentum across the globe to enable transport sustainability. However, most of these TODs are creating neighbourhood gentrification as a result of higher housing prices. Hence, the contribution of TOD policies towards sustainable transportation goals remains unclear. This paper uses Bangalore, India, as a case study to examine the effects of TOD gentrification on transit ridership. In Bangalore, station areas are witnessing the influx of large capital on condominiums, in response to TOD policies and accessibility to transit. These condominiums are expensive and attract the affluent, leading to new build gentrification. The study evaluates the impact of such new build gentrification on transit ridership. Data analysis suggests that, gentrifiers contribute significantly towards metro ridership because of the metro's high level of service (LOS). However, the other sustainable mode shares among gentrifiers are less due to poor implementation of TOD policies and the low LOS of the bus system. The study reveals that metro is attracting TOD residents, especially intermediate public transport, bus and motorbike users, whose destination are locating within walkable distance from the metro stations and the willingness to use metro is high, once the fully integrated metro network is developed. The results indicate that the transit and TOD policies in Bangalore are indeed improving transit mode shares, but to ensure equity and optimize sustainable transport mode shares, more policy interventions are required for the provision of: affordable housing and encouraging diversity in new TODs; improving neighbourhood built environment; and mode integration measures.